2000
DOI: 10.1128/jvi.74.24.11671-11680.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of the 3′ tRNA-Like Structure in Tobacco Mosaic Virus Minus-Strand RNA Synthesis by the Viral RNA-Dependent RNA Polymerase In Vitro

Abstract: A template-dependent RNA polymerase has been used to determine the sequence elements in the 3 untranslated region of tobacco mosaic virus RNA that are required for promotion of minus-strand RNA synthesis and binding to the RNA polymerase in vitro. Regions which were important for minus-strand synthesis were domain D1, which is equivalent to a tRNA acceptor arm; domain D2, which is similar to a tRNA anticodon arm; an upstream domain, D3; and a central core, C, which connects domains D1, D2, and D3 and determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 49 publications
2
51
1
2
Order By: Relevance
“…37) Osman et al have demonstrated that the tRNA-like structure is important for in vitro minus-strand RNA synthesis by the template-dependent ToMV RdRp. 38) Furthermore, deletions of the 3'-terminal sequences or the addition of extra non-viral sequences results in the loss or reduction of in vivo infectivity of tobamovirus RNA, 4),5) which indicates the importance of intact 3'-terminal structures. However, a recent study with Turnip yellow mosaic virus, which belongs to the Tymovirus genus in the alpha-like virus superfamily, suggests that aminoacylation of the genomic RNA itself is not an absolute requirement for RNA replication.…”
Section: )mentioning
confidence: 99%
“…37) Osman et al have demonstrated that the tRNA-like structure is important for in vitro minus-strand RNA synthesis by the template-dependent ToMV RdRp. 38) Furthermore, deletions of the 3'-terminal sequences or the addition of extra non-viral sequences results in the loss or reduction of in vivo infectivity of tobamovirus RNA, 4),5) which indicates the importance of intact 3'-terminal structures. However, a recent study with Turnip yellow mosaic virus, which belongs to the Tymovirus genus in the alpha-like virus superfamily, suggests that aminoacylation of the genomic RNA itself is not an absolute requirement for RNA replication.…”
Section: )mentioning
confidence: 99%
“…The roles each play during infection vary, but in general, these include regulation/enhancement of translation, replication of the genome, fidelity of the 39 end of the viral RNA, encapsidation, viral RNA genome stability, and thus overall virus amplification. Because they lie at the 39 end of the viral genome, TLSs are among the first sequences to be replicated by the RNAdependent RNA polymerases (RDRPs) and can contain promoter sequences (Dreher et al 1984;Singh and Dreher 1997;Osman et al 2000); thus they could regulate the switch between negative strand synthesis and translation. In addition, one study proposes that the valylated TYMV TLS delivers its amino acid to the ribosome to initiate translation of a viral open reading frame in cis; this model remains controversial (Barends et al 2003;Matsuda and Dreher 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Regions which were identified as being important for negative-strand synthesis in vitro included the 3Ј-terminal CA sequence, domains D1 (equivalent to a tRNA acceptor arm), D2 (similar to a tRNA anticodon arm), and D3 (an upstream pseudoknotted region), and a central core region C which connects domains D1, D2, and D3. Domain D2 and the central core region C were shown to be the most important elements for binding of the TMV RdRp complex to the viral 3Ј-TR (22).…”
mentioning
confidence: 99%
“…The 183-kDa protein, which is translated as a result of ribosomal readthrough of a termination codon at the end of the open reading frame for the 126-kDa protein, additionally has a domain typical of RNA-dependent RNA polymerases (RdRps) (14). The 35-kDa cell-to-cell movement protein and the 17.5-kDa coat protein are translated from 3Ј-coterminal subgenomic RNAs.The 3Ј-terminal region (3Ј-TR) of TMV RNA can be folded into a tRNA-like structure and adjacent upstream pseudoknots (7, 31) which have been shown to be important for TMV RNA replication in vivo (3, 28) and negative-strand RNA synthesis in vitro (22,33). Regions which were identified as being important for negative-strand synthesis in vitro included the 3Ј-terminal CA sequence, domains D1 (equivalent to a tRNA acceptor arm), D2 (similar to a tRNA anticodon arm), and D3 (an upstream pseudoknotted region), and a central core region C which connects domains D1, D2, and D3.…”
mentioning
confidence: 99%
See 1 more Smart Citation